HONG KONG LOGISTICS SKYSCRAPERS (World Science, 2018)
The publication reveals some architectural features of contemporary logistics buildings in Hong Kong with 15 and more floors, called in the article "logistics skyscrapers". These vertically developed spatial structures make it possible to preserve the urban structure compactness. At the same time they support the development of logistic business in the conditions of acute insufficiency of land for construction and a constantly growing need for logistics areas within the city boundaries, caused largely by the explosive development of the e-commerce branch. Evolution of the type is being analysed in the context of global economic interdependence and connectivity. Types of logistics skyscrapers are classified on the basis of arrangements, which are carried out through the vertical loading links.